The combination of traditional cardiorespiratory markers during treadmill testing "to failure" in athletes, depending on professional activity - V. I. Pustovoyt; E. I. Balakin; A. V. Khan; A. A. Murtazin; N. F. Maksjutov; P. S. Merkulova; K. A. Kubyshev (National Electronic Information Consortium (NEICON), 2023)
Exercise tolerance test with the use of the spiroergometry technique is a reliable diagnostic method which provides objective information about cardiorespiratory system condition when performing physical activity. Both new and traditional, well-proven cardiorespiratory markers obtained in the process of treadmill testing "to failure", are described in this article. The nature of the influence of physical exertion on the indicators of cardiorespiratory system functional activity is presented. The interpretation for planning and subsequent monitoring of the training process in athletes of various professional activities is proposed.